Evaluation of flue-gas treatment technologies for municipal waste incineration: A case study in Changzhou, China. (20th May 2018) - Wen, Zongguo; Di, Jinghan; Liu, Shutong; Han, Juan; Lee, Jason Chi Kin
Abstract: With increasing trends in using municipal waste incineration (MWI) technologies, more consideration has been given to the problem of harmful byproducts in its flue. In 2014, a new national standard for pollution control of municipal solid waste incineration was released by the Chinese government, which also gives guidance to local governments to establish their own standards. In order to evaluate whether the treatment technologies for MWI flue gas can both meet the new standard and have overall positive environmental impacts across whole life cycle, a waste life cycle assessment (LCA) was conducted for flue gas to compare treatment technologies employed in MWI plants. Based on a case study of a plant in Changzhou China, a model was established using three combinations of technologies: (a) Spray semi dry reactor + activated carbon + filter bag (Scenario 1); (b) Spray semi dry reactor + dry deacidification reactor + activated carbon + filter bag (Scenario 2); (c) selective non-catalytic reduction (SNCR) + spray semi dry reactor + dry deacidification reactor + activated carbon + filter bag (Scenario 3). The study has wide policy implications on how the industry is, or should be, regulated. Normalized results revealed that technologies used in Scenarios 1 and 2 had less overall impacts on the environment and less direct impact from emissions than those of Scenario 3. Energy-conservation and emission reduction index showed that Scenario 2 best fits current conditions and policy goals about energy consumption and air pollutant emission, despite recent regulations for the requirement of including SNCR in incineration plants. The most significant limiting factor is NOx, which is in alignment with the results of policy analysis. Integrated analysis showed that although Scenario 2 is the best choice under current circumstances, further improvement in technology are likely to meet with new standards. Policy-makers should comprehensively consider the environmental impacts of the entire life cycle instead of the one-size-fits all standard. Highlights: Contributions to environmental impacts from flue gas are mainly from NOx discharge. Use of dry deacidification has the lowest impacts, yet fails to meet the standards. Adding SNCR may increase environmental impacts over the life cycle of the facility. But new standards in China require the use of SNCR to treat NOx in flue gas. When making policies and standards, life cycle impacts should be considered.